THE COMPETITIVE ADVANTAGE OF PT. AURORA EXECUTIVE PLACEMENT CONSULTANT DURING COVID-19 PANDEMIC - Armaan Arora; Jacob Donald Tan (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
In a country of 273.8 million people, the COVID-19 pandemic has had a significant impact on the job market in Indonesia. The pandemic has caused a slowdown in economic activity and disrupted supply chains, leading to job losses, reduced hiring and retaining talent. These skill shortages have had a significant impact on the economy and businesses, as they struggle to find skilled workers to meet their demands. With the shortage in hiring PT. Aurora Executive Placement Consultant a human resource, Recruitment Company is still serving in the market because of their competitive advantage in the market as other companies in the market have failed. This research uses qualitative methods with interviews and questionnaire as the main data collection method with subjects ranging from various levels of employees, executives, and clients of PT. Aurora Executive Placement Consultant. Dynamic Database, Taylor Made For Clients, Digital Transformation, Talent Matching From Social Networking, Aggressive Direct Marketing, Communication, Industry Expertise, Pay Cut Reimbursement, and Health Protocols, Trust In Owners Integrity & Knowledgeability and Assessment Tools are some of the most impactful competitive advantages of PT. Aurora Executive Placement Consultant compared to its competitor in executive search. I would recommend for future study on executive search firms experience during the COVID-19 pandemic.